Effects of micro-structure on aerodynamics of Coccinella septempunctata elytra (ladybird) in forward flight as assessed via electron microscopy. (November 2017) - Xiang, Jinwu; Liu, Kai; Li, Daochun; Du, Jianxun
Highlights: The micro-structure was examined by a scanning electron microscope and a digital microscope. The effects of morphology on Coccinella septempunctata (Coleoptera: Coccinellidae) elytra in forward flight were investigated by numerical simulations. Camber and the local corrugation in the leading elytron edge play significant roles in improving the aerodynamic performance. Abstract: The effects of micro-structure on aerodynamics of Coccinella septempunctata (Coleoptera: Coccinellidae) elytra in forward flight were investigated. The micro-structure was examined by a scanning electron microscope and a digital microscope. Based on the experimental results, five elytron models were constructed to separately investigate the effects of the camber and the local corrugation in both leading edge and trailing edge on aerodynamics. Computational fluid dynamic simulations of five elytron models were conducted by solving the Reynolds-Averaged Navier-Stokes equations with the Reynolds number of 245. The results show that camber and the local corrugation in the leading edge play significant roles in improving the aerodynamic performance, while the local corrugation in the trailing edge has little effect on aerodynamics.